Analisis Makna Peribahasa Melayu Kepulauan Riau Dalam Video YouTube Assyria Lover - Nursila Nursila; Desi Andrea; Kasmawati Kasmawati; Zhari Abadi Adil (UIR Press, 2023)
This study examines the meaning of the Riau Islands Malay proverb which is broadcast through the official YouTube page at https://youtu.be/gkeyFZXAMso. The video which lasts five minutes and three seconds (00.05.03) describes the Malay proverbs used in the daily activities of the people of the Riau Archipelago. By using the content analysis method, the author wants to find out how the meaning of the Malay proverb used in the Assyria Lover youtube video is. Data collection techniques used are documentation techniques and listening and note-taking techniques. The analysis technique used is content analysis. The data contained in the video regarding Malay proverbs and dialogues on the Assyria Lover YouTube video can be used as evidence in conducting this research. The research begins with identifying, classifying, and interpreting data. From the results of the analysis, there are 8 proverb data including, 4 Kepulawan Riau Malay proverbs in the Assyria Lover youtube video, 3 Riau Islands Malay parables in the Assyria Lover youtube video, and 1 figurative proverb or Riau Archipelago Malay in the Assyria Lover youtube video.